Successful surgical treatment of esophageal liposarcoma (4-year follow-up) - S. Yu. Dvoreckiy; A. A. Ilin; R. P. Mishra; M. A. Dvoreckaya; A. L. Akopov (Вестник хирургии имени И.И. Грекова)
A clinical case of successful surgical treatment of a patient with a very rare esophageal liposarcoma is presented. Despite the severe early postoperative complication, tracheomediastinal fistula, a satisfactory long-term result was   achieved (4th year of follow-up).